Real‐life experience in switching to new extended half‐life products at European haemophilia centres. Issue 6 (16th August 2019) - Peyvandi, Flora; Garagiola, Isabella; Boscarino, Marco; Ryan, Aislin; Hermans, Cedric; Makris, Michael
Abstract: The concept of replacement therapy in haemophilia is changing significantly thanks to the switch from standard products to extended half‐life products. These novel drugs are showing beneficial effects overcoming current prophylaxis limitations by reducing the infusion frequency, maintaining a higher trough level to ensure a lower risk of bleeding, and making treatment significantly less distressing to patients by improving the quality of life. Real‐life data on the efficacy of novel drugs and their impact on routine management of haemophilia A and B patients are still limited. This manuscript reports the results of a European survey conducted by the European Association for Haemophilia and Allied Disorders (EAHAD) at the beginning of 2018 on the clinical management of patients using extended half‐life recombinant FVIII and FIX fusion products, since at the time of the survey none of the PEGylated products were available yet. We report data on the efficacy of these novel drugs by 33 European haemophilia centres that have already switched to extended half‐life fusion products, showing a significant reduction in the number of infusions and a satisfactory trough levels in the clinical care of haemophilia patients, with a greater impact for haemophilia B.